Strategic Planning for Hospital Management Information System (SIMRS) Dental and Oral Hospital (RSGM) Universitas Andalas (Unand) Indonesia - Suci Rahmasari; Harfindo Nismal; Yudi Setyawan; Dyana Putri; Aminatu Nur Rahmah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
In the current information era, hospitals, including dental and oral hospitals, are required to improve performance and competitiveness as a business entity by not reducing the mission it carries. Currently, computer-based management information systems are a very important supporting tool, and it could even be said to be absolutely necessary to support hospital operational management. A hospital management information system, hereinafter abbreviated as SIMRS, is a communication information technology system that processes and integrates the entire flow of hospital service processes in the form of a network of coordination, reporting, and administrative procedures to obtain precise and accurate information and is part of the health information system. Efforts to utilize information systems are a step forward that need to be implemented in the face of very rapid changes, and the impact of the era of globalization is starting to be felt. Having a health information system is very helpful in data processing activities, most of which are carried out using computers that have been programmed with various programs that will handle an application.